2012
DOI: 10.4315/0362-028x.jfp-11-433
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hypobromous Acid as a Hide-On Carcass Antimicrobial Intervention

Abstract: Escherichia coli O157:H7 and Salmonella on cattle hides at slaughter are the main source of beef carcass contamination by these foodborne pathogens during processing. Hypobromous acid (HOBr) has been approved for various applications in meat processing, but the efficacy of HOBr as a hide antimicrobial has not been determined. In this study, the antimicrobial properties of HOBr were determined by spraying cattle hides at either of two concentrations, 220 or 500 ppm. Treatment of hides with 220 ppm of HOBr redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
0
8
1
Order By: Relevance
“…No research has been found regarding the effectiveness of HA on the reduction of foodbome pathogens on postrigor beef. However, previous studies demonstrated the application of HA at a concentration of 200 ppm reduced E. coli 0157:H7 on both prerigor beef and hide-on carcass by approximately 2 log CFU/cm2 for both sites (14,27). In the current study, HA treatment resulted in less than a 1-log CFU/50-cm2 reduction for either E. coli 0157:H7 or non-0157 STEC at both high and low inoculation levels on beef surfaces before storage.…”
Section: Resultscontrasting
confidence: 58%
“…No research has been found regarding the effectiveness of HA on the reduction of foodbome pathogens on postrigor beef. However, previous studies demonstrated the application of HA at a concentration of 200 ppm reduced E. coli 0157:H7 on both prerigor beef and hide-on carcass by approximately 2 log CFU/cm2 for both sites (14,27). In the current study, HA treatment resulted in less than a 1-log CFU/50-cm2 reduction for either E. coli 0157:H7 or non-0157 STEC at both high and low inoculation levels on beef surfaces before storage.…”
Section: Resultscontrasting
confidence: 58%
“…It is unclear why HOBR did not effectively reduce bacterial populations on the surfaces of cheek meat, as our laboratory previously demonstrated that spray application of l,3-dibromo-5,5-dimethylhydantoin, which is hydrolyzed to the active hypobromous acid form in aqueous solution, reduced STEC 0157:H7 levels on beef cutaneous trunci sections and beef hearts by 1.6 to 2.1 log CFU/cm2 (20) and determined that spray application of hypobromous acid on cattle hides reduced E. coli by 2.2 to 3.8 log CFU/cm2 (30). Zhao et al (36) demonstrated that immersion of chicken skin in LEV-SDS for 1 to 5 min reduced S. enterica by 2.9 to 5.3 log CFU/cm2.…”
Section: Discussionmentioning
confidence: 90%
“…Chemicals including lactic acid, butyric acid, caprylic acid, calcium sulphate, sodium benzoate, chlorine dioxide and ozone (FDA approved) that cause 3–5 log reduction in O157 can be used to disinfect drinking water (Zhao et al, ). In addition, animal hides that often get contaminated with faecal matter during transport may be washed with hot water and acidic solutions like hypobromous acid before evisceration, which can in turn reduce O157 on hides by 2–4 logs (Bosilevac, Nou, Barkocy‐Gallagher, Arthur, & Koohmaraie, ; Schmidt, Wang, Kalchayanand, Wheeler, & Koohmaraie, ).…”
Section: Control Strategies Targeting Stec Can Also Mitigate Ar‐stecmentioning
confidence: 99%